Human Resource Management In The Digital Era - Ibrahim Ibrahim; Umar Umar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study aims to analyze the development of human resource management (HRM) practices in the digital era by reviewing research results that have been published in the last five years. The method used is a literature study, namely by collecting, reviewing, and synthesizing findings from various national and international journals related to HRM, especially those discussing organizational adaptation to changes in technology and the work environment. The results of the analysis show that digitalization has encouraged organizations to implement innovation in HRM management, such as the use of technology-based management systems, online training, and work flexibility (Putri, 2024). In addition, adaptive HRM practices have been shown to significantly increase employee motivation, satisfaction, and performance (Firmansyah, 2023). The study also found that the main challenges faced by organizations are the need for digital competency development and change management (Rahmawati, 2022). Based on these findings, it can be concluded that responsive and innovative HRM management is the key to organizational success in facing the digital era and increasing competitiveness sustainably